The case of the blazing sky - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 2008)
With the threat of prairie fires looming, security expert Hank the Cowdog takes on extra duties as Head of Fire Safety, while trying to resist the mouth-watering hens in Sally May's chicken house.